Scunthorpe Steel Action Committee, 1980 (London, 1980)
1980 1980-95 "Scunthorpe Steel Action Committee, 1980" [BW0224], 1980, Trades Union Congress In 1980, unions in the steel industry called a national strike in support of a bid for a 20% pay increase. The management had offered a 5% increase. The unions were also concerned about the British Steel Corporation plans to close some plants with the loss of thousands of jobs. The steel strike lasted nearly 14 weeks, January 2 - April 2 1980. After beginning in the nationalised sector, the stoppage gradually spread to the privatised steel works. The plants reopened after the Lever inquiry recommended a package worth 16% in return for an agreement on working practices and productivity deals. Later that summer, 17,000 of the 24,000 South Wales steel workers were put on short time and in September, the Consett works in County Durham was shut down with the loss of 3,400 jobs. By the end of 1980, BSC had completed the closure of a number of outdated and loss making plants and reduced its workforce to 130,000 - compared with a total of 268,500 employees at the time of nationalisation. This photo shows a demonstration by the Scunthorpe Steel Action Committee.